Penerapan Model Problem Based Learning Berbantuan Media Canva untuk Meningkatkan Hasil Belajar Matematika - Sari, Diah Puspita; Muhardini, Sintayana; Hadi, Erwin (Unversitas Muhammadiyah Mataram, 2023)
Abstract: As technology develops in the industrial era 4.0, it has a significant impact on the world of education. Learning is starting to be directed towards the use of learning media that is able to attract students' interest in learning. Specifically for mathematics learning in elementary school. Studying mathematics is known as a difficult, boring and monotonous lesson. Even students at elementary school level are less interested in this lesson. This can be seen from the relatively low mathematics learning outcomes. The aim of this research is to improve students' mathematics learning outcomes through the application of the Problem Based Learning (PBL) learning model assisted by Canva media. The location of this research is SDN 1 Sukamulia Timur with a sample size of 23 students in class IV. The instrument used to collect research data related to learning outcomes is a multiple choice test that uses Bloom's taxonomy. Research data analysis uses quantitative descriptive. The research results showed that there was an increase in student learning outcomes in mathematics lessons after implementing learning with the PBL model assisted by Canva. The number of students who completed (above KKM) in cycle I and cycle II increased. 80% of students are said to have completed.Abstrak: Seiring perkembangan teknologi di era industri 4.0 memberikan dampak yang signifikan terhadap dunia pendidikan. Pembelajaran mulai diarahkan menuju penggunaan media pembelajaran yang mampu menarik minat belajar peserta didik. Khusus pembelajaran matematika di SD. Belajar matematika terkenal dengan istilah pelajaran sulit, membosankan, dan monoton. Bahkan peserta didik di tingkatan SD pun kurang tertarik dengan pelajaran ini. Hal ini terlihat dari hasil belajar matematika yang tergolong rendah. Adapun tujuan penelitian ini yaitu meningkatkan hasil belajar matematika peserta didik melalui penerapan model pembelajaran Problem Based Learning (PBL) berbantuan media canva. Lokasi penelitian ini yaitu SDN 1 Sukamulia Timur dengan jumlah sampel sebanyak 23 peserta didik di kelas IV. Instrumen yang digunakan untuk mengambil data penelitian terkait hasil belajar adalah tes pilihan ganda yang menggunakan taksonomi Bloom. Analisis data penelitian menggunakan deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa terjadi peningkatan hasil belajar peserta didik pada pelajaran matematika setelah melaksanakan pembelajaran dengan model PBL berbantuan canva. Jumlah peserta didik yang tuntas (di atas KKM) pada siklus I dan siklus II mengalami peningkatan. 80% peserta didik dikatakan tuntas.